Does magnetic resonance imaging grading correlate with return to sports after bone stress injuries? A systematic review and meta-analysis - Hoenig, T.; Tenforde, A. S.; Strahl, A.; Rolvien, T.; Hollander, K. (The American Journal of Sports Medicine, 2022)
Background: While some studies have failed to reveal any significant relationship between magnetic resonance imaging (MRI) grading and return to sports after bone stress injuries, others have reported either a linear or nonlinear relationship.